DUALISM OF AUTHORITY ON ISLAMIC BANKING DISPUTE SETTLEMENT - heru wahyudi (JURNAL ILMIAH LIVING LAW, 2015)
This study aims to look at how the impact of the presence of two authority to adjudicate Islamic banking disputes, the religious courts to the publiccourt. The author conducted research normative juridical law by using four approach, tha it statute approach, conseptual approach, case approach and comparative approach. The results showed that the Islamic personality principle contained in the Act No. 3 in 2006 did not conflict with the principle of pacta sunt servanda as set forth in the Act No. 21 of 2008 in terms of the options granted by law to choose the country as a judicial dispute resolution forum of Islamic banking. Authority to examine, decide, and resolve disputes Islamic banking is the absolute authority of the courts within the Religious Courts.